KOMUNIKASI UNTUK KESEHATAN MENTAL: MENJAGA MENTAL TETAP SEHAT SELAMA PANDEMI - Suzy Azeharie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Rumah Singgah Peduli Cabang Jakarta Pusat located on Jalan Kernolong IV, No.33 RT 06 RW 08, Kenari Village, Senen Subdistrict is one of the halfway houses that serve as temporary huts for sick patients and referred to Gatot Soebroto Army Central Hospital (RSPAD) and Dr. Cipto Mangunkusumo National Central General Hospital (RSCM). The location of Rumah Singgah Peduli located in Central Jakarta is located close to the two type A Hospitals. Patients who stop are patients who come from outside the city or area and experience cost problems to pay for a layover during the treatment period. Daily contributions of Rp 10,000 are cash amounting to Rp 5,000 and dues for kitchen costs of Rp 5,000 making the limitations of halfway houses to meet the daily living needs of patients. In addition to having to go back and forth to the hospital and treatment at both hospitals, many patients are currently afraid and anxious due to the endless pandemic. In a state of illness they are made anxious about the possibility of contracting the Covid 19 virus in addition to uncertainty about the situation of this outbreak. The FIKom UNTAR Community Service PKM team conducts communication activities by holding face-to-face and playing films that aim to keep patients and their companions excited, not giving up, not afraid and always have hope for healing. In short, keep the mental health of patients awake during this pandemic. In addition, the PKM Team helps The Care Halfway House by providing a number of patient needs such as vitamins, fans and mattresses.